Even in the best of both worlds, you can't have it all: How German voters navigate the trilemma of mixed-member proportionality - Lukas Haffert; Pascal Langenbach; Tobias Rommel (Max Planck Institute for Research on Collective Goods, 2023)
The fragmentation of the party system has confronted the German mixed-member proportional electoral system with a trilemma. It can only ensure two out of three goals: proportionality, guaranteed representation of district winners, and a fixed and predictable size of the Bundestag. This paper studies how citizens position themselves in this trilemma. Using original survey data, we find that all goals are popular and no combination of goals commands majority support. This suggests that electoral reform is politically difficult not only because of the self-interest of parties but also because of widely perceived trade-offs. At the same time, our findings indicate that voters can be a constructive force for reform. More knowledgeable voters can form coherent and meaningful preferences over electoral rules. Voters are also receptive to the logical constraints of the system: informing respondents about the trilemma trade-offs in an experimental setting makes them more accepting of reform proposals.
hdl:21.11116/0000-000D-736D-8
Keywords: 330